Hello,
I have been trying to solve this problem for the last hour and haven't gotten anywhere. Got any ideas?
#1
(1 - 1/2)(1 - 1/2^2)...(1-1/n^2)=n+1/2n
Prove: (1-(1/(n+1)^2) + (n+1)/2n = (n+2)/(2n+2) for all integers >=2 (greater/equal)
#2
2^n < (n+2)!, for all integers n >= 0
Your real problem here, is that the "theorem", as stated, is not true. Specifically, if n= 2, the left side is (1- 1/2)(1- 1/4)= 1- 1/2- 1/4+ 1/8= 8/8- 4/8- 2/8+ 1/8= 9/8- 6/8= 3/8 while the right side is 2+ 1/4= 9/4, not 3/8.
Prove: (1-(1/(n+1)^2) + (n+1)/2n = (n+2)/(2n+2) for all integers >=2 (greater/equal)
#2
2^n < (n+2)!, for all integers n >= 0